Structural and Chromatic Displacement in Contemporary Tunisian Painting - Noumi, Dr. Bashar Jawad (Indonesian Journal of Cultural and Community Development, 2025)
General Background: Contemporary visual art increasingly explores conceptual transformations that challenge traditional aesthetic structures and visual conventions. Specific Background: Within this context, the concept of displacement, originally rooted in linguistic and stylistic studies, has gradually expanded into visual arts as a method for generating new artistic meanings through deviations in form, color, and structure. Knowledge Gap: Despite the theoretical significance of displacement, limited analytical attention has been given to its aesthetic manifestations within contemporary Tunisian painting. Aims: This study examines the aesthetics of displacement in the artworks of the Tunisian artist Fatima Damq in order to identify how structural and chromatic transformations construct new visual meanings. Results: The analysis of selected artworks demonstrates that displacement emerges through the interaction of color, spatial organization, and compositional vocabulary, creating dialogical visual spaces that encourage multiple interpretive readings. The structural arrangement of shapes and colors produces layered symbolic patterns that move beyond conventional pictorial representation. Novelty: The research provides an analytical framework that interprets displacement as a constructive aesthetic mechanism within contemporary Tunisian visual practice. Implications: These findings contribute to broader discussions in aesthetics and art criticism by highlighting how structural and chromatic transformations can expand interpretive possibilities in contemporary painting.